2020
DOI: 10.3390/cancers12082015
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Validation of the Italian Version of the Bt-DUX: A Subjective Measure of Health-Related Quality of Life in Patients Who Underwent Surgery for Lower Extremity Malignant Bone Tumour

Abstract: The purpose of this study was to translate the English bone tumour DUX (Bt-DUX-Eng) questionnaire for lower extremity bone tumour patients, a disease-specific quality of life (QoL) instrument, into Italian and then examine the validity of the Italian version of Bt-DUX (Bt-DUX-It). The adaptation and translation process included forward translation, back-translation, and a review of the back-translation by an expert committee. The Bt-DUX-It was validated in a sample of adolescents treated for lower extremity os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…The global quality of life at 6 months showed a decreasing trend compared to that of the start of treatment time with an average of 59.3 and 50.2 respectively. In a cohort of patients affected by musculoskeletal cancer, comparable to that of the present study, with a follow-up of more than 3 years there was a GH-QoL equal to 83.3 [23]. This data highlighted how in a more prolonged follow-up it is possible to expect a signi cant recovery in the quality of life, whereas in the initial phase this aspect is strongly reduced and presents a decreasing trend which must be considered carefully.…”
Section: Discussionsupporting
confidence: 76%
“…The global quality of life at 6 months showed a decreasing trend compared to that of the start of treatment time with an average of 59.3 and 50.2 respectively. In a cohort of patients affected by musculoskeletal cancer, comparable to that of the present study, with a follow-up of more than 3 years there was a GH-QoL equal to 83.3 [23]. This data highlighted how in a more prolonged follow-up it is possible to expect a signi cant recovery in the quality of life, whereas in the initial phase this aspect is strongly reduced and presents a decreasing trend which must be considered carefully.…”
Section: Discussionsupporting
confidence: 76%
“…Internal consistency of the seven Italian questionnaires ranging from 0.754 (21) to 0.95 (24) and they were found to be consistent with the versions translated into other languages, except for WOMAC italian questionnaire (22) that the value (cronbach alpha 0.81-0.91) was slightly lower than that of the Portuguese internal consistency (cronbach alpha 0.92-0.98) (57) version.…”
Section: Psychometric Characteristics Of Questionnaires For Lower Limbsupporting
confidence: 53%
“…The seven questionnaires identi ed for evaluating the lower limbs have reliability values ranging from 0.507 (20) to 0.99 (21) reported by GSQ and UCLA respectively. No reliability tests were performed for the Italian version of the CPG and DUX questionnaire (19,24). For other questionnaires, this psychometric variable of the Italian version is in line with versions available in other languages, observing only some small differences such as for example: The reliability of the GSQ Italian version (ICC = 0.507) is lower than the Spanish version (ICC=0.87) and the reliability of the TESS Italian version (ICC=0.99) it is higher than they looked at the Chinese (55) (ICC=0.893) and Korean (56) (ICC=0.874) versions.…”
Section: Psychometric Characteristics Of Questionnaires For Lower Limbmentioning
confidence: 99%
“…The bone tumor DUX (Bt-DUX) questionnaire is a useful tool for measuring quality of life in patients with bone tumors, which is easy to use in clinical practice. Morri et al translated the English bone tumor DUX for patients with lower extremity bone tumors into Italian, and evaluated the validity of the Italian version of Bt-DUX [ 20 ]. In their study, the Italian version showed a similar usefulness to the Dutch and English versions.…”
mentioning
confidence: 99%